2010
DOI: 10.1074/jbc.m110.167585
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mice with −6A Haplotype of the Human Angiotensinogen Gene Have Increased Blood Pressure Compared with −6G Haplotype

Abstract: Hypertension is a serious risk factor for cardiovascular disease, and the angiotensinogen (AGT) gene locus is associated with human essential hypertension. The human AGT (hAGT) gene has an A/G polymorphism at ؊6, and the ؊6A allele is associated with increased blood pressure. However, transgenic mice containing 1.2 kb of the promoter with ؊6A of the hAGT gene show neither increased plasma AGT level nor increased blood pressure compared with ؊6G. We have found that the hAGT gene has three additional SNPs (A/G a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(36 citation statements)
references
References 50 publications
(46 reference statements)
2
34
0
Order By: Relevance
“…Nucleotide sequencing of the BAC revealed that it contains haplotype I of the hAT 1 R gene. The 1.2-kb promoter of the hAT 1 R gene in this BAC was modified to haplotype II by recombineering using the 1.2-kb promoter fragment from a human subject containing haplotype II of the hAT 1 R gene as described previously for hAGT gene (18). The nucleotide sequence of the resulting BAC was confirmed by sequence analysis.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nucleotide sequencing of the BAC revealed that it contains haplotype I of the hAT 1 R gene. The 1.2-kb promoter of the hAT 1 R gene in this BAC was modified to haplotype II by recombineering using the 1.2-kb promoter fragment from a human subject containing haplotype II of the hAT 1 R gene as described previously for hAGT gene (18). The nucleotide sequence of the resulting BAC was confirmed by sequence analysis.…”
Section: Methodsmentioning
confidence: 99%
“…BP was measured in the conscious state by radio telemetry as described previously (20). After 4 days of basal blood pressure measurement, animals were treated with the AT 1 R blocker losartan (Sigma-Aldrich; 30 mg/kg/day) in drinking water as described previously (18). The blood pressure was then measured 24 h after losartan treatment.…”
Section: Primermentioning
confidence: 99%
“…The TG mice utilized in this study were generated in our laboratory as described previously by Jain et al (3). Genotyping analysis of the tail snips, followed by sequencing, was performed to confirm the genetic lineage of these TG mice.…”
Section: Methodsmentioning
confidence: 99%
“…The angiotensin II concentration in the samples was determined directly from the standard curve according to the manufacturer's protocol as described previously (3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation